2021
DOI: 10.3390/molecules26227016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial, Anticancer, PASS, Molecular Docking, Molecular Dynamic Simulations & Pharmacokinetic Predictions of Some Methyl β-D-Galactopyranoside Analogs

Abstract: A series of methyl β-D-galactopyranoside (MGP, 1) analogs were selectively acylated with cinnamoyl chloride in anhydrous N,N-dimethylformamide/triethylamine to yield 6-O-substitution products, which was subsequently converted into 2,3,4-tri-O-acyl analogs with different acyl halides. Analysis of the physicochemical, elemental, and spectroscopic data of these analogs revealed their chemical structures. In vitro antimicrobial testing against five bacteria and two fungi and the prediction of activity spectra for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Methylgalactoside was recently reported to possess potential antimicrobial activities against Bacillus subtilis, Escherichia coli, and in-silico ability to inhibit SAR-CoV-2 by binding proteases 39 . Another study by Amin et al 40 revealed that acylation of beta-D-galactopyranoside with different acyl halides resulted in methyl esters with antifungal, antibacterial and anticancer activities. Modi ed beta-D-galactopyranoside containing tri-and tetravalent glycoclusters inhibited Pseudomonas aeruginosa d-galactose-speci c lectin PA-IL (LecA); a virulence factor that is cytotoxic and also aids adhesion to host's cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Methylgalactoside was recently reported to possess potential antimicrobial activities against Bacillus subtilis, Escherichia coli, and in-silico ability to inhibit SAR-CoV-2 by binding proteases 39 . Another study by Amin et al 40 revealed that acylation of beta-D-galactopyranoside with different acyl halides resulted in methyl esters with antifungal, antibacterial and anticancer activities. Modi ed beta-D-galactopyranoside containing tri-and tetravalent glycoclusters inhibited Pseudomonas aeruginosa d-galactose-speci c lectin PA-IL (LecA); a virulence factor that is cytotoxic and also aids adhesion to host's cells 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on a strong literature report, diverse biologically effective molecules have aromatic rings, heteroaromatic rings, and aliphatic chain substituents (Amin et al 2021;Alam et al 2021aAlam et al , 2022Bulbul et al 2021a;Farhana et al 2021a;Hosen et al 2022;Kawsar et al , 2021aKawsar et al , 2022aMaowa et al 2021). It was found that benzene ring, substituted benzene ring, nitro, sulfur, and halogen-based groups are very potent to enhance the biochemical and biological activity of the carbohydratebased compound (Rana et al 2020;Islam et al 2022;Nasrin et al 2022;Kawsar et al 2021bKawsar et al , 2022bHosen et al 2021;Tahmida et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They are the source of the metabolic energy supply and are also useful for the fine-tuning of cell-cell interactions and other crucial processes (Varki 1993;Seeberger and Werz 2007). It was found from the literature survey that a large number of biologically active compounds also possess aromatic, heteroaromatic, and acyl substituents (Amin et al 2021(Amin et al , 2022Lepenies et al 2010;Rana et al 2020;Bulbul et al 2021a, b;Arifuzzaman et al 2018;Maowa et al 2021a;Alam et al 2021a). The benzene, substituted benzene, and also nitrogen, sulfur, and halogen-containing substituents are known to enhance the biological activity of the parent compound (Rana et al 2021;Farhana et al 2021a;Devi et al 2019;Alam et al 2021b).…”
Section: Introductionmentioning
confidence: 99%